Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1073/pnas.0812374106
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ binding by domain 2 plays a critical role in the activation and stabilization of gelsolin

Abstract: Gelsolin consists of six homologous domains (G1-G6), each containing a conserved Ca-binding site. Occupation of a subset of these sites enables gelsolin to sever and cap actin filaments in a Ca-dependent manner. Here, we present the structures of Ca-free human gelsolin and of Ca-bound human G1-G3 in a complex with actin. These structures closely resemble those determined previously for equine gelsolin. However, the G2 Ca-binding site is occupied in the human G1-G3/actin structure, whereas it is vacant in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(153 citation statements)
references
References 31 publications
5
147
1
Order By: Relevance
“…This ␤-sheet edge thus gets exposed and forms an interface with the G3 domain. In addition, Asp-259 (in g2-g3 linker) has been shown to initiate a helix formation in coordination with Thr-260 and condense the otherwise disordered linker to allow close packing of G2 and G3 (7,48). Interestingly, an Asp-260 and Thr-261 are also present at similar positions in this linker region of severin, but the smaller length of this linker or the other specific residues like proline might result in the calcium sensitivity of severin.…”
Section: Discussionmentioning
confidence: 99%
“…This ␤-sheet edge thus gets exposed and forms an interface with the G3 domain. In addition, Asp-259 (in g2-g3 linker) has been shown to initiate a helix formation in coordination with Thr-260 and condense the otherwise disordered linker to allow close packing of G2 and G3 (7,48). Interestingly, an Asp-260 and Thr-261 are also present at similar positions in this linker region of severin, but the smaller length of this linker or the other specific residues like proline might result in the calcium sensitivity of severin.…”
Section: Discussionmentioning
confidence: 99%
“…The clear imaging of breaks permits quantitative analyses of severing as well. The technique has been applied to examine the biochemical activity of proteins like plasma gelsolin (Nag et al, 2009) and budding yeast twinfilin (Moseley et al, 2006). In a landmark study, Andrianantoandro and Pollard (2006) demonstrated direct severing by cofilins from fission yeast, Acanthamoeba, and human.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the immense difficulty posed by researchers in attaining diffraction quality crystals of gelsolin at different pH conditions. Interestingly, the two crystal structures of the Ca 2ϩ -activated actinbound N-terminal G1-G3 half of gelsolin were obtained in buffers containing pH 4.7 (29,42). The Ca 2ϩ ion at its binding site in the G2 domain is now resolved in the human gelsolin-actin complex (42), but it could not be resolved in the equine gelsolin (29), which led to questions about how the activation/complexation occurred.…”
Section: Saxs Data Analysis-measured Saxs I(q)mentioning
confidence: 99%